Advancing patient age is associated with worse outcomes in low‐ and intermediate‐grade primary chondrosarcoma of the pelvis. Issue 4 (27th January 2020) - Houdek, Matthew T.; Witten, Brent G.; Hevesi, Mario; Griffin, Anthony M.; Salduz, Ahmet; Wenger, Doris E.; Sim, Franklin H.; Ferguson, Peter C.; Rose, Peter S.; Wunder, Jay S.
Abstract: Background: Conventional primary pelvic chondrosarcoma often presents as a low‐ or intermediate‐grade tumor in older patients. Although this is the most common variant of pelvic chondrosarcoma, studies examining treatment outcomes are lacking. The purpose of this study was to evaluate patients with these tumors to determine their outcomes of treatment. Methods: Seventy‐three patients (grade I [n = 19, 26%] and grade II [n = 54, 74%]) were reviewed including 55 (75%) males and 18 (25%) females, with a mean age of 51 (range, 17‐81) years and follow‐up of 9 ± 5 years. Results: The 10‐year disease‐specific survival was 71%. Grade II disease (hazard ratio [HR], 6.74; P  = .04) and age ≥50 years (HR, 3.97; P  = .02) was associated with death due to disease. The 10‐year local recurrence‐ and metastatic‐free survival were 79% and 72%. Of the patients with a local recurrence (n = 11), 7 (64%) recurred at a higher histological grade. Patient age ≥50 years was associated with local recurrence (HR, 10.03; P  = .02) and metastatic disease (HR, 4.20; P  = .02). Conclusion: Advancing patient age was an independent risk factor for worse survival and disease recurrence. Tumors often recurred locally at a higher grade and as such wide local excision remains the treatment of choice for these tumors.